STRUKTUR KEPEMILIKAN, CORPORATE GOVERNANCE, DAN AGENCY COST - Tyara Dwi Putri (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2018)
The research examines the influence of ownership structure, corporate governance and agency cost on corporate at Indonesian Stock Exchange.Panel data is used in this research. Type of ownership is determined by managerial ownership and institutional ownership. Corporate governance measured by number of director and percentage of independent commissioners. Proxy of agency cost is expense ratio. The results of this study show that institutional ownership and number of director reduces the agency cost significantly.